P150 ULCERATING CMV ESOPHAGITIS – A UNIQUE COMPLICATION OF ACHALASIA. (23rd November 2019) - Corvinus, F; Neumann, H; Babic, B; Kovalets, I; Grimminger, P
Abstract: Aim: Ulcerating CMV associated esophagitis in an immuncompetent patient has not been described before. This case report highlights diagnostic pitfalls in differentiating achalasia from pseudo achalasia. Background & Methods: A 41-year-old man presented to the high resolution manometry lab with progressive retrosternal dysphagia and regurgitation. Endoscopy revealed a dilated esophagus with a passable stenosis of the esophagogastric junction. Between 27 to 39 cm a deep 3 x 12 cm ulcer reaching the lamina muscularis was detected. Biopsies were taken and processed to the institute for pathology and microbiology. A barium swallow revealed typical features of achalasia. A dilated hypomotile esophagus and a beak sign were seen. Histopathology described a deep ulcer with a mixed inflammatory infiltration without any signs for malignancy. The virology finally revealed a strong positivity for CMV in PCR. Therefor the diagnosis of CMV esophagitis was made. Reasons for an immunodeficiency (HIV, Trypanosoma pallidum etc.) could be excluded. After endoscopic placement of a probe, high resolution manometry was performed. It showed a disturbed EGJ relaxation, an enhanced residual pressure (IRP) and panesophageal pressurizations in almost every swallow. These are typical features of Type II Achalasia (Chicago Classification v 3.0). Results: The patient received antiviral therapy (Ganciclovir) for 2 months. Only a moderate symptom relief was achieved. Endoscopic reevaluation showed a complete remission of the huge esophageal ulcer. There was no esophageal scar or other reason for EGJ obstruction. CMV was no longer detected. A second high resolution manometry confirmed again a Type II Achalasia. The patient underwent laparoscopic myotomy an 180° degree fundoplication. 6 months after the intervention the patient is well and has a complete remission of his symptoms. Conclusion: Although ulcerating CMV esophagitis may be a cause of pseudoachalasia, in this case for the first time primary achalasia is described to be the reason for ulcerating CMV esophagitis.